Concrete plates with externally bonded FRP under contact detonations. (6th December 2021) - Mourão, R.; Caçoilo, A.; Teixeira-Dias, F.; Lecompte, D.; Stratford, T.
Abstract: Local damage on concrete elements subjected to a contact detonation include spalling and cratering of the back and front face, respectively. This paper presents the results of a detailed experimental and numerical methodology aiming to analyse the influence of externally bonded fibre reinforced polymers (FRP) on the spalling phenomena of concrete when it is subjected to contact explosions. The influence of externally bonded reinforcement (EBR) on the diameter and depth of the spalling is experimentally investigated, as is also the total momentum transferred to the ejected fragments when their mass increases. The experimental observations enable the development of a computational framework, where a finite element (FE) model is validated and used to perform a through-thickness analysis focused on the stress wave propagation and associated damage mechanisms. It is found that the extent of concrete volumetric damage is highly influenced by the mass of the bonded material, as well as increased bonded areas leading to enlarged surface damage. Additionally, it was verified that the compressive strength of concrete plays a major role in the spall damage. Highlights: The response of concrete with externally bonded FRP under contact detonation is discussed. Volumetric damage in concrete is highly dependent on mass of bonded material. Increasing bonded areas leads to spread of surface damage. Compressive strength of concrete is major factor in spall damage.